Phytochemical characterization and anti-inflammatory activity of a water extract of Gentiana purpurea roots. (30th January 2023) - Zhang, Lin; Ulriksen, Emilie Steinbakk; Hoel, Håvard; Sandvik, Lene; Malterud, Karl Egil; Inngjerdingen, Kari Tvete; Inngjerdingen, Marit; Wangensteen, Helle
Abstract: Ethnopharmacological relevance: Gentiana purpurea was one of the most important medicinal plants in Norway during the 18th and 19th centuries, and the roots were used against different types of gastrointestinal and airway diseases. Aim of the study: To explore the content of bioactive compounds in a water extract from the roots, a preparation commonly used in traditional medicine in Norway, to assess the anti-inflammatory potential, and furthermore to quantify the major bitter compounds in both roots and leaves. Materials and methods: G. purpurea roots were boiled in water, the water extract applied on a Diaion HP20 column and further fractionated with Sephadex LH20, reverse phase C18 and normal phase silica gel to obtain the low molecular compounds. 1D NMR, 2D NMR, and ESI-MS were used for structure elucidation. HPLC-DAD analysis was used for quantification. The inhibition of TNF-α secretion in ConA stimulated peripheral blood mononuclear cells (PBMCs) was investigated. Results: Eleven compounds were isolated and identified from the hot water extract of G. purpurea roots. Gentiopicrin, amarogentin, erythrocentaurin and gentiogenal showed dose-dependent inhibition of TNF-α secretion. Gentiopicrin is the major secondary metabolite in the roots, while sweroside dominates in the leaves. Conclusions: The present work gives a comprehensive overview of the major low-molecular weight compounds in the water extracts of G. purpurea, including metabolites produced during the decoction process, and show new anti-inflammatory activities for the native bitter compounds as well as the metabolites produced during preparation of the crude drug. Graphical abstract: Image 1 Highlights: Gentiana purpurea was one of the most popular Norwegian medicinal plants. The roots have a high content of secoiridoid glucosides. Erythrocentaurin and gentiogenal were produced during the decoction process. Native secoiridoids and degradation products show anti-inflammatory activity.